Integrating climate-smart rice agriculture into secondary-level curriculum: lessons from three high schools in the Philippines - Manalo, Jaime A.; Balmeo, Katherine P.; Berto, Jayson C.; Saludez, Friedierick M.; Villaflor, Jennifer D.; Pagdanganan, Argie M. (Springer, 2016)
Climate change (CC) is an urgent and highly relevant topic that must be integrated into the school curriculum. Literature on CC integration, however, is scarce, let alone literature on integrating climate-smart rice agriculture (CSRA). Bringing CSRA lessons into the classroom means the chance is higher that climate-smart technologies on rice will reach even the most far-flung areas of the Philippines, which stand to be among the most vulnerable as regards the negative impacts of CC. This paper shares experiences drawn from three high schools in the Philippines on integrating CSRA into their curriculum. The research centers on appropriate teaching tools/strategies, push and exogenous factors in CSRA integration, and the types of information that are likely to be shared by the students with their farmer-parents or other farmers in their communities. Surveys among participating students (n = 155) and three focus group discussions among key school officials were conducted. Different teaching methods and/or tools were found to be generally useful in various contexts. Photos and videos, however, emerged as the most effective tools across sites. The livelihood source of the students does have a bearing on the complexity of messages that they can convey. Students from rice-farming households can competently discuss even highly complex adaptation and mitigation information with their farmer-parents or other farmers. Thorough message-framing is necessary to maximize student involvement as well as to increase production of education–entertainment (edutainment) materials to be utilized in teaching. This study, in general, contributes to CC education by bringing in best-fit practices in teaching tools and strategies to mobilize students to act on urgent matters relating to the impacts of CC. It also advises on considering exogenous factors that might affect CC education by taking into account those that are equally capable of shaping students’ perception and knowledge.